Mediating effect of an eco-control system on the relationship between a proactive environmental strategy and environmental performance in Jordan - Alastal, Ahmad Yahia Mustafa (2021)
Environmental performance is a set of measures that describe an organization's success in reducing and minimising its environmental impact. It is among the factors that reflect the organization's corporate social effectiveness in terms of environmental processes, programs, and policies. The objectives of the current study are to investigate the relationship between proactive environmental strategy and environmental performance, examine the relationship between a proactive environmental strategy and the use of an eco-control system, examine the relationship between the use of an eco-control system and environmental performance, and examine the mediating effect of the use of the eco-control system on the relationship between proactive environmental strategy and environmental performance in Jordan. The use of an eco-control system was proxied by the levers of control framework, which include the belief control system, boundary control system, diagnostic control system, and interactive control system. The data were collected from 94 service and industrial listed organizations in Jordan. The Partial Least Squares Structural Equation Modelling program was used to analyse two hundred thirty-one questionnaires. The findings showed a significant and positive relationship between proactive environmental strategy and environmental performance in Jordan. Furthermore, the finding revealed a significant and positive relationship between proactive environmental strategy and the use of an eco-control system. It has also shown a significant and positive relationship between the use of an eco-control system and environmental performance. Lastly, the use of an eco-control system significantly mediates the relationship between proactive environmental strategy and environmental performance in Jordan. The study can help Jordanian organizations and government officials improve their knowledge about environmental issues and how they can save and protect the environment by implementing environmental strategies, especially proactive environmental strategies that go beyond the regulations and compliance to reduce the impact of the organizations on the environmental performance. Using an eco-control system helps an organization to use its resources efficiently and effectively to improve environmental performance. Future studies could test the relationship's applicability to other developing countries and give attention to other control systems to examine the mediating effect on the relationship between proactive environmental strategy and environmental performance.